2022
DOI: 10.1371/journal.pone.0271065
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of spontaneous onset of labor at term (PREDICT study): Research protocol

Abstract: Background Recent studies have shown that elective induction of labor versus expectant management after 39 weeks of pregnancy result in lower incidence of perinatal complications, while the proportion of cesarean deliveries remains stable, or even decreases. Still, evidence regarding collateral consequences of the potential increase of induction of labor procedures is still lacking. Also, the results of these studies must be carefully interpreted and thoroughly counter-balanced with women’s thoughts and opinio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The rates of CS (16.7% [n = 31] vs. 24.1% [n = 47], RR 0.7 [95% CI: 0.5-1.0], p = 0.07) and a composite of adverse neonatal outcomes (9.7% [n = 18] vs. 14.4%…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of CS (16.7% [n = 31] vs. 24.1% [n = 47], RR 0.7 [95% CI: 0.5-1.0], p = 0.07) and a composite of adverse neonatal outcomes (9.7% [n = 18] vs. 14.4%…”
Section: Resultsmentioning
confidence: 99%
“…In the exploratory analyses, these women had the lowest rate of CS, 12.4%, although the difference to 16.4% in women in the early induction group was not statistically significant. Predicting the probability of spontaneous onset of labor is difficult and research on the subject is needed, 24 but in our opinion, cervical status at the screening visit may serve as a useful basis for discussion with the pregnant woman.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, machine learning algorithms have been developed to predict various aspects of spontaneous childbirth, including premature birth, [33][34][35] mode of delivery, 36 fetal growth management, 37 pregnancy complications, 38 perinatal health management, 39 labor onset and delivery, 40 birth outcomes, 41 and labor progression. 6,42,43 While several systematic reviews have indicated the potential of AI and machine learning approaches in prenatal care (Table 1), they also highlight the need for further research for widespread clinical implementation.…”
Section: Machine Learning Prediction Algorithmsmentioning
confidence: 99%